Integrating Qur’anic Thematic Exegesis and Legal Regulation in Resolving Waqf Disputes in Indonesia - Mukhtar Yunus (Journal Analytica Islamica, 2023)
Throughout 2023, there was a significant increase in waqf disputes in Indonesia, indicating a complex interaction between social customs, positive law, and religious traditions. Using thematic interpretation techniques and legal provisions for resolving waqf litigation in Indonesia, this study seeks to examine the acculturation of Qur’anic values. Employing a qualitative research method with a normative-sociological legal approach, this study analyzes primary data in the form of laws and regulations related to waqf, religious court decisions in 2023, and interviews with actors involved in waqf protection and dispute resolution. The findings show that waqf dispute resolution in Indonesia in 2023 was dominated by issues related to the ownership status of waqf land, the determination of nazir, and the use of waqf benefits that contradicted the objectives of the waqif. The thematic interpretation of Qur’anic verses related to waqf, particularly QS. Ali ‘Imran [3]: 92, QS. al-Baqarah [2]: 261, and QS. al-Baqarah [2]: 271, produces an understanding that waqf is a multidimensional form of worship containing spiritual, social, and economic dimensions. The acculturation of these Qur’anic values with positive legal regulations, particularly Law Number 41 of 2004 concerning Waqf and the regulations of the Indonesian Waqf Board, creates a framework for dispute resolution based on the principles of benefit, justice, and the preservation of waqf assets. This study recommends the need to harmonize public religious understanding with positive legal regulations through waqf education based on thematic interpretation and by strengthening the role of the Indonesian Waqf Board in mediating waqf disputes.